Cruzando los Andes (1890-1891). Fannie B. Ward’s Writings About Peru in the Postwar Era - Morales-Pino, Ainaí (2024)
Afloat on Lake Titicaca! How the very name recalls schooldays and geography lessons, though in this early time, when we located unpronounceable names on the map of a country which to our young imagination did not exist anywhere but on paper, we had no idea of proving their reality by a personal visit. It is amusing to remember what incorrect pronunciation of most of these South American names the teachers laboriously drilled into us; and the fact remains in our best schools, by names which the residents of the places would hardly recognized.